Architecture of Russian Avant-Garde and Japanese Metabolism: Parallels of Forms and Meanings - Konovalova, Nina (project baikal, 2019)
Russian avant-garde of the 1920-ies and Japanese metabolism of the 1960-ies are close to each other in their fundamental ideas and major concepts of morphogenesis: the removal of the distinction between form and content, architectural structures, combining forms of the building and its functional purpose, the relations of the architectural structures with the city and nature. Japanese architects not only studied the Russian avant-garde and were fond of its ideas, but also developed them, bringing to life what existed only in the projects and sometimes seemed unrealizable utopia. It is because of innovative research and experiments that make up the essence of architectural creativity and the Russian avant-garde, and Japanese metabolism, they have had, and still have a great influence on the world professional architectural community.
Keywords: architecture of Russian avant-garde; Japanese metabolism; shaping in architecture; architecture of the XX century